2018
DOI: 10.4314/agrosh.v18i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of maize farmers' access to agricultural information in Aiyedire local government area, Osun State, Nigeria

Abstract: This study analyses maize farmers' access to agricultural information in Aiyedire Local Government Area of Osun state, Nigeria. The specific objectives of this study were to describe the socioeconomic characteristics of the maize farmers, identify access of maize farmers to agricultural information, determine the level of access to agricultural information and identify the sources of agricultural information to the maize farmers. A structured questionnaire was used to randomly sample 105 respondents used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
1
1
Order By: Relevance
“…Marital status: The findings also revealed that majority of adopters (76.0%) and non-adopters (54.2%) were married, while only 3.5% of the adopters were divorcees and 8.5% of non-adopters being widows suggesting that greater proportions of pearl millet farmers in the study area were married. This goes in line with Adebayo et al, (2018) that majority of maize farmers in Aiyedire…”
Section: Sources Of Datasupporting
confidence: 83%
“…Marital status: The findings also revealed that majority of adopters (76.0%) and non-adopters (54.2%) were married, while only 3.5% of the adopters were divorcees and 8.5% of non-adopters being widows suggesting that greater proportions of pearl millet farmers in the study area were married. This goes in line with Adebayo et al, (2018) that majority of maize farmers in Aiyedire…”
Section: Sources Of Datasupporting
confidence: 83%
“…Treatment of seeds with fungicides reportedly reduces Aspergillus species contamination of groundnut [34]. Responses on agronomic practices of farmers in this study show that none of the farmers treated their seeds before planting contrary to farmers studied in the Southwestern part of Nigeria [35] where maize farmers of Aiyere regularly accessed treated maize seed for planting. Findings of this study further reveals that sourcing of planted seeds from the open market can significantly influenced aflatoxin concentration of produce.…”
Section: Discussioncontrasting
confidence: 54%
“…The available storage facilities can potentially impact production capacity as it introduces concerns regarding post-production storage logistics. Previous research by [31] and [32] has demonstrated the significance of storage facilities for agricultural output and trade. Farmers may experience losses and lower incomes if they are unable to store their harvests properly and retain their quality.…”
Section: Discussionmentioning
confidence: 99%